How to make recommendation systems fair: An adequate utility-based approach - Roengchai Tansuchat; Olga Kosheleva (Asian Journal of Economics and Banking (AJEB), 2022)
Purpose - In user-oriented websites, e.g. in news websites or in seller websites, it is important to take the user's preferences into account when deciding which items to place in higher-exposure locations. The traditional approach to solving this problem, based on maximizing the average user utility, leads to unfair solutions, and this eventually hurts the company's bottom line. Because of this, researchers have proposed complex schemes that explicitly add fairness to the formulation of this problem. But since utilities already describe human preferences, it is strange that it is necessary to add something beyond utilities. Design/methodology/approach - In this paper, the authors analyze the problem of selecting exposure level for different items from the viewpoint of decision theory, the basic theory underlying all our activities, including economic ones. Findings - The authors show that a more adequate use of utilities, namely, taking into account that Nash's bargaining solution is a proper way to make group decisions, not maximizing average utility, already leads to fair solutions. Originality/value - The idea to apply Nash's bargaining solution to the problem of assigning exposure level to different items is new, as well as the analysis that shows that this application restores the fairness, which is missing in the current solutions.
Keywords: 330; Recommendation systems; Fairness; Utility